The art of teaching music - Jorgensen, Estelle R. (Indiana University Press, 2008)
The Art of Teaching Music takes up important aspects of the art of music teaching ranging from organization to serving as conductor to dealing with the disconnect between the ideal of university teaching and the reality in the classroom. Writing for both established teachers and instructors on the rise, Estelle R. Jorgensen opens a conversation about the life and work of the music teacher. The author regards music teaching as interrelated with the rest of lived life, and her themes encompass pedagogical skills as well as matters of character, disposition, value, personality, and musicality. She reflects on musicianship and practical aspects of teaching while drawing on a broad base of theory, research, and personal experience. Although grounded in the practical realities of music teaching, Jorgensen urges music teachers to think and act artfully, imaginatively, hopefully, and courageously toward creating a better world. - Publisher.